The influence of work culture through mediating employee loyalty on employee performance - Surifah, Ade; Mukhsin, Moh; Imron, Ali (Jurnal Mantik, 2025)
The problem often faced by XYZ Hospital is the poor performance of employees. The purpose of this study is to analyze a model that is expected to improve employee performance by involving work culture with employee loyalty as an intervening variable in nurses at XYZ Hospital Serang. The research method used is a quantitative method using a questionnaire tool with an interval scale of 1-10 with a sample of 126 nurses from a population of 350 employees to test the five (5) hypotheses that have been set. The Structural Equation Model-Partial Least Square (SEM-PLS) model is used to test the statistical significance of the path coefficient. The results of this study indicate that work culture has a positive and significant effect on employee performance, work culture has a positive and significant effect on Employee Loyalty, Employee Loyalty has a positive and significant effect on Employee performance, and Employee Loyalty mediates the effect of Work Culture on employee performance